The eye of the storm - De Circasia, Victor (Torino : Associazione Velan, 2000)
Bouveret, Philippe ; Cabiati, Vincenzo ; Caro, Anthony ; Cordero, Riccardo ; Deacon, Richard ; Di Rosa, Richard ; Fisher, Joel ; Gastini, Marco ; Gomez, Susy ; Hall, Nigel ; King, Phillip ; Kneale, Bryan ; Lovato ; Mach, David ; Maeda, Noriaki ; Minoli, Paolo ; Pan, Robert ; Randall-Page, Peter ; Tucker, William ; Venet, Bernar
The eye of the storm, Villa dei Laghi - Parco La Mandria (Torino), 7 ottobre - 12 novembre 2000
boek